2001
DOI: 10.1046/j.1365-8711.2001.05005.x
|View full text |Cite
|
Sign up to set email alerts
|

The distance to Supernova 1998aq in NGC 3982

Abstract: The distance to NGC 3982, host galaxy to the Type Ia supernova SN 1998aq, is derived using 32 Cepheids discovered in archival multi‐epoch Hubble Space Telescope observations. Employing recent Large Magellanic Cloud Cepheid period–luminosity relations and absolute zero‐point, we find a distance to NGC 3982 of , including both random (r) and systematic (s) uncertainties, and ignoring any metallicity dependence in the Cepheid period–luminosity relation. Still unpublished light curve photometry promises to make … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…We also used these observations to search for additional Cepheids in the hosts which previously had the smallest numbers of Cepheids: NGC 3021, NGC 3982, NGC 4536, and NGC 4639 (L. M. Macri et al 2011a, in preparation). The new observations, together with those from Riess et al (2009b), Saha et al (1996Saha et al ( , 1997Saha et al ( , 2001), Gibson et al (2000), Stetson & Gibson (2001), and Macri et al (2006), provide the position, period, and phase of 730 Cepheids in eight hosts with reliable SN Ia data as well as NGC 4258. The Cepheids in each host were typically imaged on 14 epochs in F 555W and 2-5 epochs with F 814W (except for NGC 4258, which has 12 epochs of F 814W data).…”
Section: Wfc3 Observations Of Cepheids In the Sh0es Programmentioning
confidence: 86%
“…We also used these observations to search for additional Cepheids in the hosts which previously had the smallest numbers of Cepheids: NGC 3021, NGC 3982, NGC 4536, and NGC 4639 (L. M. Macri et al 2011a, in preparation). The new observations, together with those from Riess et al (2009b), Saha et al (1996Saha et al ( , 1997Saha et al ( , 2001), Gibson et al (2000), Stetson & Gibson (2001), and Macri et al (2006), provide the position, period, and phase of 730 Cepheids in eight hosts with reliable SN Ia data as well as NGC 4258. The Cepheids in each host were typically imaged on 14 epochs in F 555W and 2-5 epochs with F 814W (except for NGC 4258, which has 12 epochs of F 814W data).…”
Section: Wfc3 Observations Of Cepheids In the Sh0es Programmentioning
confidence: 86%
“…To account for possible differences in the Cepheid photometry measured with ACS and WFPC2, we compared the photometry of 8711 non-variable stellar sources in the field of NGC 3982 observed with both cameras through F 555W and F 814W . Using the master catalog of WFPC2 photometry used by Gibson et al (2000) and Stetson & Gibson (2001) we find the mean difference between our WFPC2 and ACS V − I colors of these sources to be 0.054 ± 0.005 mag (WFPC2 is bluer), with no dependence on source color or magnitude. The origin of this difference largely resides in the specific zeropoints adopted by Stetson & Gibson (2001) and those from Riess et al (2009) and Macri et al (2006Macri et al ( ,2009.…”
Section: Sky Determination and Bias Correctionmentioning
confidence: 80%
“…Using the master catalog of WFPC2 photometry used by Gibson et al (2000) and Stetson & Gibson (2001) we find the mean difference between our WFPC2 and ACS V − I colors of these sources to be 0.054 ± 0.005 mag (WFPC2 is bluer), with no dependence on source color or magnitude. The origin of this difference largely resides in the specific zeropoints adopted by Stetson & Gibson (2001) and those from Riess et al (2009) and Macri et al (2006Macri et al ( ,2009. Because our goal is limited to placing the WFPC2 Cepheid colors on the same photometric scale as the ACS data to measure distances relative to NGC 4258, we corrected the WFPC2 Cepheid data of Gibson et al (2000) for NGC 4639, NGC 4536, and NGC 3982 to the ACS color scale.…”
Section: Sky Determination and Bias Correctionmentioning
confidence: 80%
“…Using a P − L relation based on ∼650 Cepheids located in the Large Magellanic Cloud that were observed by the Optical Gravitational Lensing Experiment (OGLE) (Udalski et al 1999), the HKP team concluded that µ = 31.56 ± 0.08 (Stetson et al 2001). More recently Riess et al (2005) used the Advanced Camera for Surveys on the HST to obtain a Cepheid distance.…”
Section: Observational Data and Uvoir Light Curvesmentioning
confidence: 99%